Antigenic and pathogenicity activities of Ralstonia solanacearum race 3 biovar 2 molecularly identified and detected by indirect ELISA using polyclonal antibodies generated in rabbits. (February 2018) - Behiry, Said I.; Mohamed, Abeer A.; Younes, Hosny A.; Salem, Mohamed Z.M.; Salem, Abdelfattah Z.M.
Abstract: Eight molecular-characterized isolates of Ralstonia solanacearum from potato belonging to race 3 biovar 2, their virulence were evaluated on potato cv. Lady Rosette, tomato cv. Strain B, eggplant cv. Balady and pepper cv. Balady and showed high virulence on potato and tomato, and lower virulence on eggplant and pepper. A laboratory study conducted to produce polyclonal antibodies against the potato brown rot bacterium; R. solanacearum cells were generated in female New Zealand white rabbits. A modification were made on the technique of indirect enzyme-linked immunosorbent assay (ELISA) to improve the sensitivity of detection, including antigenic and sensitivity to R. solanacearum race 3 biovar 2 isolates. Determination of the optimum period to collect the antiserum (including, polyclonal antibodies) showed that the best collection dates were at 14, 3 and 7 days, in that order. The efficiency of the antiserum was compared among 42 isolates that cause potato brown rot disease; our polyclonal antiserum (14 days) reacted positively with all tested isolates at a dilution of 1:6.4 × 10 3 . Data indicated the different reactions of eight R. solanacearum isolates at various dilutions (1:1.6 × 10 3 to 1:5.12 × 10 6 ) at 14 days against polyclonal antiserumat a concentration of approximately 1 × 10 8  CFU/mL and we found the lowest detection level by the indirect ELISA technique was 10 6  CFU/mL. Finally we recommended the reasonable sensitivity results of the ELISA technique to detect the bacterial pathogen given than the cost of this technique if much lower than that of other expensive molecular techniques. Graphical abstract: Image 1 Highlights: 8 R. solanacearum isolates (race 3 biovar 2), and their virulence were evaluated. Polyclonal antibodies was generated in female New Zealand white rabbits. The indirect ELISA was used to detect of R. solanacearum race 3 biovar 2. ELISA showed that the best collection dates for antiserum were at 14, 3 and 7 days. Polyclonal antiserum (14 days) reacted positively with all tested isolates.